2015
DOI: 10.4049/jimmunol.1402689
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 Promotes Myeloid-Derived Suppressor Cell Recruitment and Bacterial Persistence during Staphylococcus aureus Orthopedic Implant Infection

Abstract: Staphylococcus aureus (S. aureus) is a leading cause of human prosthetic joint infections (PJIs) typified by biofilm formation. We recently identified a critical role for myeloid-derived suppressor cells (MDSCs) in S. aureus biofilm persistence. Pro-inflammatory signals induce MDSC recruitment and activation in tumor models; however, the mechanisms responsible for MDSC homing to sites of biofilm infection are unknown. Here we report that several cytokines (IL-12p40, IL-1β, TNF-α, and G-CSF) and chemokines (CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
196
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(221 citation statements)
references
References 72 publications
19
196
3
3
Order By: Relevance
“…To evaluate the importance of strain on infection outcome and inflammation, we compared three commonly used S. aureus isolates, namely, LAC, MW2, and UAMS-1, in a mouse model of orthopedic-implant biofilm infection that models PJI in humans. As previously reported in our laboratory with USA300 LAC (25)(26)(27), this is a well-established low dose infection model associated with rapid bacterial expansion, with titers most prominent in the soft tissue surrounding the infected knee joint followed by the tendons/ligaments comprising the joint, femur, and implant (Fig. 1).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…To evaluate the importance of strain on infection outcome and inflammation, we compared three commonly used S. aureus isolates, namely, LAC, MW2, and UAMS-1, in a mouse model of orthopedic-implant biofilm infection that models PJI in humans. As previously reported in our laboratory with USA300 LAC (25)(26)(27), this is a well-established low dose infection model associated with rapid bacterial expansion, with titers most prominent in the soft tissue surrounding the infected knee joint followed by the tendons/ligaments comprising the joint, femur, and implant (Fig. 1).…”
Section: Resultsmentioning
confidence: 78%
“…As previously described in our S. aureus PJI model (25,26), the innate immune response is predominantly composed of MDSCs (50 to 80% of the CD45 ϩ population), which persist throughout infection ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Similarly, during a chronic S. aureus orthopedic biofilm infection, Heim et al (22,23) observed an expansion of IL-10-producing MDSCs at the site of infection, which was associated with bacterial persistence. Targeted depletion of these cells resulted in an enhanced proinflammatory response that resulted in increased bacterial clearance (23,24).…”
mentioning
confidence: 99%